2023
DOI: 10.1002/pc.27435
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the physical properties of poly(lactic acid) through the addition of thermoplastic polyurethane and functionalized short carbon fibers

Abstract: The elevated brittleness of commercial grades of poly(lactic acid) (PLA) may limit their use in several engineering applications. Therefore, the aim of this work is to develop a PLA-based material possessing well-balanced stiffness and toughness. Composites were prepared by blending PLA with increasing contents (from 10 to 30 wt%) of a thermoplastic polyurethane (TPU) and a fixed concentration (5 wt%) of carbon fibers (CFs), to tune the mechanical properties of the resulting materials. In order to increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…(Venice, Italy) as a unidirectional fabric having an aerial density of 217 g/m 2 and an average fiber diameter of 7 μm. PCL (density = 1.1 g/cm 3 , molecular weight [M w ] = 80,000 g/mol) was provided by Polysciences, Inc. (Warrington, PA, USA) in the form of 3-mm pellets, and it was used as the interfacial self-healing agent. Poly(vinyl alcohol) (PVA, density = 1.2 g/cm 3 , M w = 50,000 g/mol) and polysorbate 80 (Tween ® 80) (density = 1.1 g/cm 3 , pH = 5.5-7.5, Brookfield viscosity 400-620 cps) were used as stabilizers in the preparation of PCL nanoparticles, and were both provided by Sigma Aldrich (Saint Louis, MO, USA) as a water soluble powder and a yellowish viscous liquid, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Venice, Italy) as a unidirectional fabric having an aerial density of 217 g/m 2 and an average fiber diameter of 7 μm. PCL (density = 1.1 g/cm 3 , molecular weight [M w ] = 80,000 g/mol) was provided by Polysciences, Inc. (Warrington, PA, USA) in the form of 3-mm pellets, and it was used as the interfacial self-healing agent. Poly(vinyl alcohol) (PVA, density = 1.2 g/cm 3 , M w = 50,000 g/mol) and polysorbate 80 (Tween ® 80) (density = 1.1 g/cm 3 , pH = 5.5-7.5, Brookfield viscosity 400-620 cps) were used as stabilizers in the preparation of PCL nanoparticles, and were both provided by Sigma Aldrich (Saint Louis, MO, USA) as a water soluble powder and a yellowish viscous liquid, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This occurs only if a good interfacial adhesion has been achieved, in order to allow an effective load transfer from the matrix to the fibers. 2,3 The interphase can be considered as an intermediate volume between the matrix and fibers, and it plays a crucial role for the mechanical properties of the composites. 4,5 This region has been often considered isotropic and homogeneous but recently, it has been discovered that it is composed by a multiphase structure with peculiar properties.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it has been demonstrated that adding substances such as poly(1,3‐propylene glycol citrate), 14 acid‐treated carbon fibers, 15 and e‐lignin 16 is a feasible approach for enhancing toughness and modifying PLA.…”
Section: Introductionmentioning
confidence: 99%